Implementasi Kebijakan Penerapan Sistem Poin Dalam Mengurangi Pelanggaran Siswa SD Al Ma’soem Bandung - Muhammad Rizky Pratama; Husni Mubarok; Dewi Permatasari; Erika Wisni Putri; M. Rohman (Educational Consultant & Counseling Career (EC3) Mataram, 2021)
The purpose of this study was to determine the application of the point system in solving students who violated the rules at SD Al Ma'soem Bandung. The approach used is a qualitative approach with a descriptive method. The results of this study indicate that the four levels which include notification, reprimand, warning and punishment in the application of the point system at SD Al Ma'soem Bandung apply in different forms. At the announcement stage, socialization during MOS (Student Orientation Period), distribution of point system circulars, pictures and publication of regulations in each class. There are direct warnings and indirect warnings at the warning stage. There are verbal and written warnings during the warning phase. In the punishment stage, the school stops activities, home visits and returns to parents. The implementation of this policy has a different impact on each student who violates the rules, but based on observations and interviews with informants (students), this policy provides a deterrent effect for students not to violate them again.